Nanomedicines Targeting Metabolism in the Tumor Microenvironment - Ren, Mengdi; Zheng, Xiaoqiang; Gao, Huan; Jiang, Aimin; Yao, Yu; He, Wangxiao (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer cells reprogram their metabolism to meet the growing demand of bioenergy and biosynthesis. The metabolic profile of cancer cells usually includes dysregulation of main nutritional metabolic pathways and the production of metabolites, which leads to tumor microenvironment (TME) having the characteristics of acidity, hypoxic and/or nutrients depletion. Targeting metabolism therapeutically has become an active and revolutionary research topic for anti-cancer drug development. The differential metabolic vulnerabilities between tumor cells and other cells within TME provides nanotechnology a therapeutic window of anti-cancer. In this review, we will present the metabolic characteristics of intrinsic cancer cells and TME, and summarize representative strategies of nanoparticles in metabolism-regulating anticancer therapy. Then, we put forward the challenges and opportunities of using nanoparticles in this emerging field.